E-Learning in Music: A Case Study of Learning Group Composing in a Blended Learning Environment. (5th February 2016) - Ruokonen, Inkeri; Ruismäki, Heikki
Abstract: New educational technology has become an important part of modern teacher education in Finland today. Studying music in Finnish teacher education means both studying music didactics and developing musical skills. With only a limited number of contact lessons in the regular curriculum, new learning environment solutions with new technology are needed. This is a qualitative case study of 16 students' experiences of studying group composing in a blended learning environment. The purpose of the study is to enrich face-to face, teacher-led learning in music with new technology and the e-learning environment and to develop a new technology-based blended learning model for student teachers' needs. The research questions considered the kind of learning experiences students had in studying music, especially group composing in a blended learning environment and how a blended learning environment can help students learning music in a creative learning process. The research is a qualitative approach to students' (16) experiences of a new blended learning environment. The blended learning method used was the rotation method, in which students learn through a schedule of independent online study in the "Rockway" music-e-learning environment, other informal online learning environments, social media and face-to-face classroom time during a 5 credit points music course. The qualitative data has been collected during the studies through group interviews and reflective writings of students' learning experiences that took place after the course. The data has been analysed by content analysis. The major advantage of blended learning is that it offers more opportunities for independent and constructive learning. The experiences of a blended learning environment were positive and the teacher's role was seen as an important and helpful mentor for more independent learning and creative learning in groups. According to students' experiences, the greatest benefit from e-learning was achieved by those who already had some musical background before these studies. The use of information and communication technologies improved students' attitudes towards independent learning concerning their musical skills.